2010
DOI: 10.1177/0143624410389396
|View full text |Cite
|
Sign up to set email alerts
|

An examination of UKCIP02 and UKCP09 solar radiation data sets for the UK climate related to their use in building design

Abstract: The climate is changing, both globally and in the UK. To adapt effectively, engineers and planners need as much information as possible on how the climate will evolve. The UK Climate Impacts Programme (UKCIP) provided this in 2002 with UKCIP02 and the latest data UKCP09, which provides data to a resolution of 5 km square grids over the UK. Data sets from these were used in this study along with the historical measured data for three locations -Bracknell (London), Manchester and Edinburgh -to analyse critically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…e) How will the estimated changes in HCED affect the cost of energy to 23 householders, and how will this depend on the HVAC systems used? 24 A c c e p t e d M a n u s c r i p t 6 Compared to recent studies aiming at developing synthetic weather files for use in building 1 energy simulations in future climates [24][25][26][27][28][29], the current work shows several important 2 advances. The future air temperature data set is built on 3-hourly observations, without a need 3 to assume any predefined diurnal temperature behaviour.…”
Section: Submitted To Energy and Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…e) How will the estimated changes in HCED affect the cost of energy to 23 householders, and how will this depend on the HVAC systems used? 24 A c c e p t e d M a n u s c r i p t 6 Compared to recent studies aiming at developing synthetic weather files for use in building 1 energy simulations in future climates [24][25][26][27][28][29], the current work shows several important 2 advances. The future air temperature data set is built on 3-hourly observations, without a need 3 to assume any predefined diurnal temperature behaviour.…”
Section: Submitted To Energy and Buildingsmentioning
confidence: 99%
“…Based on previous work [42], hourly data of W and RH were 9 constructed using several iterations, as described in [43]. 10 11 Besides the approach used in this paper, an option for downscaling climate model data to the 12 required hourly time resolution is the usage of a stochastic weather generator [27] [44]. In the 13 first stage of the current study, we did indeed make trials with a weather generator, but 14 difficulties arose in reproducing the observed high correlations between summertime 15 temperature and solar radiation.…”
Section: Submitted To Energy and Buildingsmentioning
confidence: 99%
“…The UKCP09 projections suggest substantial increases in sunshine duration and solar radiation, but less downward diffuse radiation [ Tham et al ., ]. Further research is needed to establish how these changes might combine in future Tw and hence to ascertain the rivers and reaches that would benefit most from riparian shade management.…”
Section: Discussionmentioning
confidence: 99%
“…the potential for extreme storms) is perhaps more important to river (Foster, 2001;Hiscock et al, 2011;Iverson and Major, 1986;Loveless et al, 1996;Macdonald et al, 2012;Schweckendiek et al, 2014;Wols and van Thienen, 2014 (Hemer et al, 2013;Woolf and Wolf, 2010) Moderate Increased storminess (severity, frequency, sequence) (Karunarathna et al, 2014) Low Wave direction (mean) Low Salinity (Holliday et al, 2010) Low Acidity (Turley et al, 2010) Low Temperature, solar radiation and drought Earth embankments and other 'soil' and 'vegetation'-based infrastructure Extremes of temperature (cold, hot, extreme dry periods) (Blenkinsopp and Fowler, 2007;Burke et al, 2010;Karoly and Scott, 2006;Murphy et al, 2009;Rahiz and New, 2013;Tham et al, 2011;Vidal and Wade, 2009) infrastructure than changes in mean flows. This is because changes in the morphology of the catchment is most responsive to individual storm events and any associated increased erosion (including scour around bridges, embankments, bends, etc.)…”
Section: Changes In Rainfall and The Impact On River Infrastructurementioning
confidence: 99%